Comprehensive Treatment of Trans-Arterial Chemoembolization Plus Lenvatinib Followed by Camrelizumab for Advanced Hepatocellular Carcinoma Patients - Juanfang Liu; Zhen Li; Wenguang Zhang; Huibin Lu; Zhanguo Sun; Guozheng Wang; Xinwei Han (Frontiers Media S.A., 2021)
Aim: This study aimed to report the efficacy and safety of trans-arterial chemoembolization (TACE) plus lenvatinib and camrelizumab in patients with advanced hepatocellular carcinoma (HCC).Methods: This retrospective study enrolled 22 patients with advanced HCC from March 2018 to December 2019. All the patients received comprehensive treatment with TACE plus lenvatinib followed by camrelizumab. Overall survival (OS) and progression-free survival (PFS) were calculated and analysed using the Kaplan-Meier method and log-rank test. Treatment response and adverse events (AEs) were also evaluated.Results: The objective response rate (ORR) and disease control rate (DCR) for the whole cohort were 68.2 and 100% at the first month and 72.7 and 95.5% at the third month, respectively. The median OS was 24 months (95% CI, 20.323-27.677 months), and the median PFS was 11.4 months (95% CI, 8.846-13.954 months). The majority of treatment-related adverse reactions were mild or moderate, except for 4 that developed to grade 3-4 (3 reactions of grade 3, 1 reaction of grade 4). No deaths or other serious adverse reactions occurred.Conclusion:Trans-arterial chemoembolization plus lenvatinib and camrelizumab shows good results incontrolling tumour progression and prolonging median OS in patients with advanced HCC.